DESCRIPTION OF KNOWLEDGE ABOUT REPRODUCTION HEALTH AND PERCIEVED BEHAVIOUR CONTROL SEXUAL IN ADOLESCENT AT GAJAHMUDA SOCIETY SELOJARI - Nurya Kumalasari; Rizki sahara (The Shine Cahaya Dunia Kebidanan, 2022)
Background; The adolescent phase is a phase with delinquency, especially sexuality. Sexuality is still considered taboo, resulting in a lack of knowledge among teenagers, so that more teenagers have engaged in sexual behavior before marriage. Purpose; to description of reproductive health education on knowledge Method; The research method is a descriptive study approach. The sample is youth youth in Selojari with a total sample of 46. Analyzed by determining the frequency distribution. Results; The results showed that the age group was 16-18 years, with the majority gender being female. Knowledge of reproductive health is in the good category of 11.8%. The perception of good behavior control is 51.8%. Conclusion; The level of knowledge of adolescents about reproductive health mostly has a sufficient level of knowledge, namely 58.8% (27 people), and the prevention is good at 51.8%.